2018
DOI: 10.1080/00016489.2018.1424999
|View full text |Cite
|
Sign up to set email alerts
|

The choice of stimulation strategy affects the ability to detect pure tone inter-aural time differences in children with early bilateral cochlear implantation

Abstract: The ability to detect ITD was present only when the cochlear implant stimulation had FS. The LF sound was more difficult to localize than the BB sound and ITD ability of FS strategies did not affect the localization ability of either sound. A low ILD seems necessary to improve the localization ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…This suggests that exposure to weakly informative but robust and consistent cues in everyday life might prompt CI listeners to learn to localize even low-frequency sounds (26). Our data support the recent study by Elköf and Tidelhom (21), who reported that half of their FSP population had ITD perception within the physiological range. The participants in their group were all of young age (8-13 years) and had been implanted bilaterally prior to their third year of age.…”
Section: Ild and Itd Perceptionsupporting
confidence: 89%
See 2 more Smart Citations
“…This suggests that exposure to weakly informative but robust and consistent cues in everyday life might prompt CI listeners to learn to localize even low-frequency sounds (26). Our data support the recent study by Elköf and Tidelhom (21), who reported that half of their FSP population had ITD perception within the physiological range. The participants in their group were all of young age (8-13 years) and had been implanted bilaterally prior to their third year of age.…”
Section: Ild and Itd Perceptionsupporting
confidence: 89%
“…However, it is unclear whether this negative finding resulted from a low number of low-frequency fine-structure channels since this was not reported. Recently, Eklöf and Tideholm ( 21 ) found that half of the CI listeners with FSP had ITD perception within the physiological range (10/20; mean threshold of 330 ± 250 μs) compared to none in the group without fine-structure (FS) coding. Although some FSP listeners appeared to have ITD sensitivity, this stimulation protocol did not improve their low-frequency sound localization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Med-El recipients these intensities are mapped to a lower portion of the patients' dynamic range and will produce CI stimulation over a wider range of electrical amplitude (Vaerenberg et al 2014). Localization via CIs is thought to be dominated by ILDs (Seeber & Fastl 2008), even in children where fine structure strategies facilitate some degree of ITD sensitivity (Eklöf & Tideholm, 2018). Since Med-El systems apply less compression to sounds louder than 65 dB SPL compared to Cochlear or Advanced Bionics, ILD cues may have been better preserved for children using Med-El systems in the present study.…”
Section: Rms Error Is Plotted Against Age At Test Inmentioning
confidence: 99%
“…Representations of temporal fine structure also differ between systems and might feasibly influence a user's ability to exploit ITDs (Eklöf & Tideholm, 2018;Thakkar et al, 2018). It is therefore important to control for differences in implant and speech processing characteristics when examining localization outcomes.…”
Section: Introductionmentioning
confidence: 99%